Variation in Care in the Management of Children With Crohn's Disease: Data From a Multicenter Inception Cohort Study. Issue 7 (2nd January 2019) - Krishnakumar, Chenthan; Ballengee, Cortney R; Liu, Chunyan; Kim, Mi-Ok; Baker, Susan S; Baldassano, Robert N; Cohen, Stanley A; Crandall, Wallace V; Denson, Lee A; Dubinsky, Marla C; Evans, Jonathan; Gokhale, Ranjana; et al.
Abstract: Background: Variation in care is common in medical practice. Reducing variation in care is shown to improve quality and increase favorable outcomes in chronic diseases. We sought to identify factors associated with variation in care in children with newly diagnosed Crohn's disease (CD). Methods: Prospectively collected data from a 28-site multicenter inception CD cohort were analyzed for variations in diagnostic modalities, treatment, and follow-up monitoring practices, along with complicated disease outcomes over 3 years in 1046 children. Generalized linear mixed effects models were used to investigate the intercenter variations in each outcome variable. Results: The mean age at diagnosis was 12 years, and 25.9% were nonwhite. The number of participants ranged from 5 to 112 per site. No variation existed in the initial diagnostic approach. When medication exposure was analyzed, steroid exposure varied from 28.6% to 96.9% ( P < 0.01) within 90 days, but variation was not significant over a 3-year period ( P = 0.13). Early anti–tumor necrosis factor (anti-TNF) exposure (within 90 days) varied from 2.1% to 65.7% ( P < 0.01), but variation was not significant over a 3-year period ( P > 0.99). Use of immunomodulators (IMs) varied among centers both within 90 days ( P < 0.01) and during 3 years of follow-up ( P < 0.01). A significant variation was seen at the geographic level with follow-up small bowel imaging and colonoscopy surveillance after initial therapy. Conclusions: Intercenter variation in care was seen with the initial use of steroids and anti-TNF, but there was no difference in total 3-year exposure to these drugs. Variation in the initiation and long-term use of IMs was significant among sites, but further research with objective measures is needed to explain this variation of care. Small bowel imaging or repeat colonoscopy in CD patients was not uniformly performed across sites. As our data show the widespread existence of variation in care and disease monitoring at geographic levels among pediatric CD patients, future implementation of various practice strategies may help reduce the variation in care. Video Abstract: